REAKSI PASAR TERHADAP PENGUMUMAN MERGER DAN AKUISISI: STUDI EMPIRIS PADA PERUSAHAAN-PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - admin, MIRNA BUDI RAHMASARI B11111079 (Jurnal Manajemen Update, 2016)
A merger is the combining of two or more companies and then combine into one company that has been exist before. It makes one of companies name that have been merger should be eliminated.While, acquisition is purchasing all or part of ownership a company, can be using acquisition of share namely purchase the company share using voting on cash, share, and other securities in the company or acquisition of asset which is purchasing all or part asset of company that have been acquisition. The purpose of this research to analyze there is any happen market reaction before and after the announcement of merger and acquisition. Market reaction can be measured using abnormal of stock return and trading volume activity, so investor can using the announcement of merger and acquisition as a consideration to invest. The population of this study is the companies that already go public that listed in Indonesian Stock Exchange that doing merger and acquisition in the period 2010-2014, while sample that used in this study are 55 companies that using purposive sampling. The analyze method that use the is test different two average that using event window, which is 10 days before the announcement of merger and acquisition and 10 days after the announcement of merger and acquisition. The result of this study show that the result of wilcoxon signed rank test has no significant difference on abnormal return and trading volume activity before and after the announcement of merger and acquisition. While, in the result of one sample t-test show that has no difference on abnormal return before and after the announcement of merger and acquisition, but the different result on the analysis of trading volume activity, that is significant difference before and after the announcement of merger and acquisition. Keywords: Merger and Acquisition, Abnormal Return, Trading Volume Activity